Restoration of perivascular adipose tissue function in diet‐induced obese mice without changing bodyweight. (31st January 2017) - Xia, Ning; Weisenburger, Sabrina; Koch, Egon; Burkart, Martin; Reifenberg, Gisela; Förstermann, Ulrich; Li, Huige
Abstract : Background and Purpose: We have recently shown that a reduced function of endothelial nitric oxide synthase (eNOS) in the perivascular adipose tissue (PVAT) contributes crucially to obesity‐induced vascular dysfunction in mice. The current study was conducted to test the hypothesis that vascular dysfunction in obesity can be reversed by in vivo improvement of PVAT eNOS activity. Experimental Approach: Male C57BL/6J mice were fed a high‐fat diet (HFD) for 22 weeks to induce obesity. During the last 4 weeks of HFD feeding, the obese mice were treated p.o. with the standardized Crataegus extract WS® 1442, which has been shown previously to improve eNOS activity. Key Results: Diet‐induced obesity in mice markedly reduced the vasodilator response of thoracic aorta to acetylcholine in wire myograph experiments. Strikingly, this vascular dysfunction was only evident in PVAT‐containing aorta but not in PVAT‐free aorta. In vivo treatment of obese mice with WS® 1442 had no effect on body weight or epididymal fat mass, but completely restored the vascular function of PVAT‐containing aorta. Feeding a HFD led to a reduced phosphorylation and an enhanced acetylation of PVAT eNOS, both effects were reversed by WS® 1442 treatment. Conclusion and Implications: PVAT plays a key role in vascular dysfunction in diet‐induced obese mice. Not obesity itself, but a PVAT dysfunction is responsible for obesity‐induced vascular disorders. Improving PVAT function by pharmacological means (e.g. with WS® 1442) can ameliorate vascular function even without reducing body weight or fat mass. Linked Articles: This article is part of a themed section on Molecular Mechanisms Regulating Perivascular Adipose Tissue – Potential Pharmacological Targets? To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v174.20/issuetoc